Symmetric and asymmetric dynamic characterization of mode‐III fracture in epoxy/unidirectional carbon‐fibre composites. Issue 3 (10th September 2019) - Bertorello, Carlos; Viña, Jaime; Bonhomme, Jorge; Viña, Isabel; Mollón, Victoria; Argüelles, Antonio
Abstract: This paper experimentally analyses the delamination behaviour of a composite material under mode III fracture as a function of the loading mode applied during the fatigue tests was carried out in two different ways. First, the test specimens were loaded cyclically in a single direction of delamination until reaching a certain fracture energy and subsequently returning to the starting point. Second, cyclic loading was applied both in one direction of delamination and in the opposite direction until reaching the same fracture energies, though in two opposite directions. The experimental results revealed clear differences in the fatigue behaviour of the material when the way of applying the load varied. In both cases, a statistical analysis of the results was carried out in order to evaluate the existing differences more suitably. Furthermore, a fractographic analysis was conducted for both types of loading in order to distinguish possible differences at the microstructural level.